Spectral analysis of Sr 3d XPS spectrum in Sr‐containing hydroxyapatite. (28th September 2020) - Komai, Shiori; Hirano, Mitsuhiro; Ohtsu, Naofumi
Abstract : The Sr 3d X‐ray photoelectron spectroscopy (XPS) spectrum of Sr‐containing hydroxyapatite (SHAp) overlaps completely with the P 2p spectrum. Thus, the chemical state identification of Sr in SHAp is a challenging task. In this work, the Sr 3d spectrum was isolated from the overlapping spectra for analyzing the chemical state of Sr using a generic peak‐fitting method. The SHAp layers containing various Sr concentrations were produced on a Ti substrate using a chemical treatment process with a calcium phosphate slurry that included Sr (NO3 )2 . The distribution of the constituent elements changed according to the Sr concentration, implying that the chemical state of Sr varied with concentration. The isolation of the Sr 3d XPS spectrum was conducted via spectral deconvolution using the P 2p spectrum corresponding to HAp. The isolated Sr 3d spectrum revealed that the chemical state of Sr was in SrO and Sr‐substituted HAp states, and their ratio varied with the Sr concentration in the layer. The SrO to Sr‐substituted HAp ratios affected the Sr ion releasing behavior from the SHAp layer, supporting the validity of the obtained analytical results.